The Impact of Digital Marketing, Price, Interior Design, and Taste on Repeat Purchase Decisions at Fadhil Songka Restaurant - Pakidi, Raodah Tuljanna; Maszudi, Edi; Ikbal, Muhammad (Manunggal Halim Jaya, 2026)
Various factors influence consumer repurchase decisions in the culinary sector, but few studies have quantitatively measured their individual contributions. This study aims to examine the influence of digital marketing, price, interior design, and taste on repurchase decisions at Fadhil Songka Restaurant, Palopo City. The approach employed was a quantitative explanatory design, utilizing survey data from 205 randomly selected consumers. The results of the partial regression analysis showed that all four variables had a positive and statistically significant effect on repurchase decisions (p < 0.05). Simultaneously, the research model was statistically significant (F = 34.268, p < 0.001) and explained 39.5% of the variance in repurchase behavior (R² = 0.395). These findings underscore the importance of optimizing digital marketing strategies, establishing competitive prices, and enhancing aspects of the dining experience, including interior design and food quality. Future research is recommended to explore other factors that influence customer loyalty in the culinary industry.